EXERCISE AND NEUROGENESIS - Mehmet Ünal (İstanbul Tıp Fakültesi Dergisi)
Neurogenesis is a biological process characterized by the formation of new neurons. During embryogenesis, neural stem cells multiply, migrate, and differentiate into mature neurons that will eventually form the central nervous system. After proliferation, differentiation, and displacement, it has been proven that, during exercise, new neurons in the dentate gyrus settle in the neural circuits of the hippocampus and brain areas that are important for memory consolidation and learning. During and after exercise, the triggering factor for exercise-induced neurogenesis is a molecule called brain-derived neurotrophic factor, also known as BDNF in recent publications. Being a member of the neurotrophin family, BDNF is vital for many functions involved in neurogenesis, including proliferation, differentiation, maturation, and survival. Besides BDNF, signal pathways molecules, such as insulin-like growth factor-1, fibroblast growth factor 2, and vascular endothelial growth factor, have also proven to be effective in neuroplasticity and hippocampal neurogenesis. During physical activities, the most affected brain region is the hippocampus. Aerobic exercises have been found to significantly increase the size and function of the human hippocampus, especially when performed with moderate exercise; it is important to ensure that the exercise is not stressful. Stress suppresses neurogenesis by increasing the release of glucocorticoids in the hypothalamic–pituitary–adrenal axis and thus prevents the formation of new neurons. If voluntary exercise exceeds a certain threshold and become exhaustion, neurogenesis is prevented via the same mechanism. Therefore, it is important that exercise is done according to each person’s ability and should not cause exhaustion.